IN VITRO ANTAGONISTIC EFFECTS OF TRICHODERMA SPP. ON SEVERAL SOILBORNE PLANT PATHOGENIC FUNGI (Journal of Sciences, Islamic Republic of Iran)
In vitro studies with Trichoderma spp., soil-borne fungal antagonists, demonstrated that a number of isolates produced volatile and non-volatile metabolites capable of inhibiting the growth and sporulation of several soil-borne plant pathogenic fungi. Microscopic observations showed that T. harzianm and T. viride, isolated from soil samples from Ahwaz and Karaj, adversely affected the mycelial growth of Rhizoctonia solani, the causal agent of seed, root rot and damping-off of bean, by hyphal contact, coiling, penetration, necrosis, lysis and in some cases fraginentation of the pathogen hyphae. T. harzianum hyphae grew parallel to those of Phytophthora drechsleri, the causal agent of root rot of cucumber, and produced appendages that attached themselves to P. drechsleri hyphae. Isolates of T. harzianum from Ahwaz and T. viride from Shahriar , Karaj, significantly reduced the germination of pseudosclerotia of Colletotrichum coccodes, the causal agent of brown stem, root rot and black dot of potato. The Ahwaz isolate of T. harzianum inhibited mycelial growth and germination of Phytophthora erythroseptica, the causal agent of pink rot of potato tubers, without penetrating the pathogen hyphae. Trichoderma spp. also reduced the mycelial growth and spore germination of Fusarium solani, the causal agent of black root rot of chickpea